Evaluation of stability of canned quail egg with organic sales and preservatives - Casas, Nidia (2016)
The quail egg is a product with high nutritional value, their shelf life is short, and is widely used in the meat products industry, by the above, a product ready to eat becomes a good alternative. The aim of this work was to evaluate the effect of salts and organic acids on the stability of canned quail egg during storage. The project was divided into two phases, the first effect of a combination of salts (NaCl and KCl) in three concentrations (2, 3 and 4%) with two concentrations of citric acid and malic acid (0.25 and 0.50% w / v) evaluating sensory quality and physicochemical characteristics after 10 days of storage. In the second phase was estimate of shelf life of the best treatments in the first stage at three temperatures. 15, 25 and 37 ° C for 90 days, evaluating sensory, chemical and microbiological changes. The results of the first phase showed that the addition of salts has a direct relationship with weight loss and hardening of the cuticle. The treatments that obtained the best scores in the sensory characteristics were 2% of salts with 0.25% citric acid and 3% salt with 0.25% malic acid. The conservation alternative presented here increase in 8 months the shelf life of the product with sensory and microbiological characteristics for suitable for marketing.